Current controversy: analysis of the 2013 FINA World Swimming Championships - Cornett, A.; Brammer, C.; Stager, J. (Medicine & Science in Sports & Exercise, 2015)
Anecdotal reports regarding the 2013 Fédération Internationale de Natation World Swimming Championships held in Barcelona suggested that swimming performances were biased, presumably because of a current.